Deciphering the Active Compounds and Mechanisms of Qixuehe Capsule on Qi Stagnation and Blood Stasis Syndrome: A Network Pharmacology Study. (27th February 2020) - Huang, Yu-Xi; Xu, Ding-Qiao; Yue, Shi-Jun; Chen, Yan-Yan; Tao, Hui-Juan; Fu, Rui-jia; Xing, Li-Ming; Wang, Taiyi; Ma, Yu-ling; Wang, Bao-An; Tang, Yu-Ping; Duan, Jin-Ao
Abstract : Background . Qixuehe capsule (QXH), a Chinese patent medicine, has been demonstrated to be effective in the treatment of menstrual disorders. In traditional Chinese medicine (TCM) theory, qi stagnation and blood stasis syndrome (QS-BSS) is the main syndrome type of menstrual disorders. However, the pharmacodynamic effect of QXH in treating QS-BSS is not clear, and the main active compounds and underlying mechanisms remain unknown. Methods . A rat model of QS-BSS was established to evaluate the pharmacodynamic effect of QXH. Thereafter, a network pharmacology approach was performed to decipher the active compounds and underlying mechanisms of QXH. Results . QXH could significantly reduce the rising whole blood viscosity (WBV) and plasma viscosity (PV) but also normalize prothrombin time (PT), activated partial thromboplastin time (APTT), thrombin time (TT), and fibrinogen (FIB) content in QS-BSS rats. Based on partial least-squares-discriminant analysis (PLS-DA), the low-dose QXH-intervened (QXH-L) and the high-dose QXH-intervened (QXH-H) groups seemed the most effective by calculating the relative distance to normality. Through network pharmacology, QXH may improve hemorheological abnormality mainly via 185 compounds-51 targets-28 pathways, whereas 184 compounds-68 targets-28 pathways were associated with QXH in improving coagulopathy. Subsequently, 25 active compounds of QXH were verified by UPLC-Q/TOF-MS. Furthermore, 174 active compounds of QXH were shared in improving hemorheological abnormality and coagulopathy in QS-BSS, each of which can act on multiple targets to be mainly involved in complement and coagulation cascades, leukocyte transendothelial migration, PPAR signaling pathway, VEGF signaling pathway, and arachidonic acid metabolism. The attribution of active compounds indicated that Angelicae Sinensis Radix (DG), Paeoniae Radix Rubra (CS), Carthami Flos (HH), Persicae Semen (TR), and Corydalis Rhizoma (YHS) were the vital herbs of QXH in treating QS-BSS. Conclusion . QXH can improve the hemorheology abnormality and coagulopathy of QS-BSS, which may result from the synergy of multiple compounds, targets, and pathways.